Species composition and abundance of Butterflies (Rhopalocera) in Ba Vi National Park, Ha Tay province - Phuong, Bui Xuan; Monastyrskii, A.L. (Academia Journal of Biology, 2015)
The study was carried out during the period from February to November of 1996 in the Bavi national park of Hatay province, North Vietnam. There were 141 butterfly species belonging to 10 families and 82 genera of Rhopalocera inhabiting in the Bavi mountain. There were 3 new butterfly species for Vietnam, such as: Celaenorrinus sp., Halpe sp. (Hesperiidae) and Dodona ouida Moore (Riodinidae). On the whole, the Bavi mountains appeared to be a suitable place for founding the national butterfly reserve in North Vietnam for faunistic and biological investigations and scientific tourism development.